Inclusion of tilapia (Oreochromis niloticus) by-product meal in the diet for red sea bream (Pagrus major, Temminck & Schlegel) fingerlings - Takakuwa, Fumiaki; Migita, Takanobu; Tanaka, Toshiko; Ukei, Junya; Iizuka, Taisuke (Fisheries science, 2025)
Considering the increasing importance of fishmeal made from processed fish residues and the high production of tilapia, this study examined the effects of substituting tilapia by-product meal (TBM) for the protein in Peruvian anchovy meal (PAM) in the diet of juvenile red sea bream ( Pagrus major ), focusing on growth and body composition. Five isonitrogenous and isolipidic diets were prepared by replacing PAM with TBM at 0, 15, 30, 45, and 55% (named as T0, 15, 30, 45, and 55, respectively). Thirty fish (mean body weight, 10.8 g) were accommodated into 500 L tanks in triplicate. In the 6-week feeding trial, no significant differences were observed in growth performance depending on the dietary TBM level ( p > 0.05). In contrast, the crude fat content of the whole body decreased linearly with increasing dietary TBM levels, with a significant difference between the T55 and T0 groups ( p < 0.05). Serum high-density lipoprotein concentration also tended to increase linearly with increasing dietary TBM levels. Overall, PAM in the diet of juvenile red sea bream could be replaced by up to 45% with TBM without any adverse effects on its growth and physiology over a 6-week period.